Blockchain technology development and use case business applications - Soon, Andrew Tongxin (Nanyang Technological University, 2022)
With the growing hype on cryptocurrencies and the rise of Non-Fungible Tokens(NFT) markets, more spotlight has been shed on blockchain-based applications in various industries such as fintech. However, there is still a lack of awareness of blockchain and people often limit blockchain to financial transactions. Until today, building and developing blockchains are very difficult since there are few frameworks and applications that support them. This is similar to the early days of the internet when people are reluctant to adapt and accept the use of the new technology. Over time, the internet has come to be essential in our everyday lives and is heavily integrated into businesses globally. Like the internet, blockchain has the potential to revolutionise the way we exchange value, transfer ownership and verify transactions. Hence, the purpose of this project is to develop a blockchain-based technology that can demonstrate how a blockchain works, how it can improve cyber security, and how it enhances trust in the cyber world. This project aims to improve people’s understanding of the technology and convince people of its benefits.